Skrb za zdravje in varnost zaposlenih v Mestni knjižnici Ljubljana - Štrempfelj, Suzana (Knjižnica, 2018)
Care for health and safety at work is a key element for ensuring a healthier, more productive and longer working life. As workers, we spend a fair amount of time at workplace, which means that our work and working environment have a direct impact on our health. Coping with psychosocial risks and stress, and health and safety at work are therefore important factors, which the employer is also legally bound to ensure. The main purpose of the contribution is to determine whether the Ljubljana City Library and its management are taking action to ensure health and safety of the employees, which activities are already being implemented and what more could be done to improve the situation in this area. The overview is based on theoretical background and the examination of activities, which are already being implemented in the context of the employee health care. The contribution consists of three parts. The first part entails the analysis of activities that were already being implemented at the Ljubljana City Library. The second part consists of a proposal for a health promotion plan, the aim of which is to inform and raise awareness, as well as to motivate employees and management to consciously and actively implement and participate in health promotion activities. The third part comprises examples of good practices and proposals for activities to improve health promotion. It is evident that in the Ljubljana City Library many other activities, besides those that are legally required, are implemented to improve the promotion of their employees% health. Much has already been done but there is still plenty of space for the proposed activities, which would help improve the health and increase the safety of the employees at the Ljubljana City Library.
Keywords: dejavnosti promocije zdravja; health at work; health care; health promotion; health promotion activities; promocija zdravja; public libraries; skrb za zdravje; splošne knjižnice; zdravje pri delu